Disaster Nursing Competencies among Nurses Working in Tertiary Level Teaching Hospital in Kathmandu, Nepal - Neupane, Hricha; Chapagain, Parikshit (Journal of Karnali Academy of Health Sciences, 2021)
Background: Nepal is prone to multiple types of natural hazards directly affecting human lives. The first responders and the largest health workforce of any country are nurses. Therefore, it is essential to determine the competencies of nurses, as one of the baseline for disaster preparedness. This study aims to explore the roles and responsibilities of nurses’ with regard to disaster management, along with nurses’ perception of core competencies and barriers to develop those competencies.Methods: Cross-sectional descriptive method was used to collect data among 234 nurses of Tribhuvan University Teaching Hospital which was chosen randomly. Stratified proportionate sampling was then done to calculate samples from each wards which was then followed by random sampling of the participants. Self-administered structured questionnaire was used to collect data. Data was analyzed using descriptive statistics (mean, frequency and SD).Results: The mean score of nurses’ roles and responsibilities in disaster management was found to be very low for all items of the questionnaire. Most of the nurses’ assumed their highest role to identify education and training needs for disaster management. However, nurses’ opinion to develop the core competencies is high for all items. All the barriers studied were identified as barriers for developing disaster competencies. The highest barrier was found the lack of training in workplace.Conclusions: It is noteworthy that nurses’ opinion of their roles and responsibility in disaster management is very low despite of their high opinion towards developing core competencies. It may be due to the barriers perceived at workplace.